2016
DOI: 10.1007/s12520-016-0453-6
|View full text |Cite
|
Sign up to set email alerts
|

Sourcing nonnative mammal remains from Dos Mosquises Island, Venezuela: new multiple isotope evidence

Abstract: Archeological excavations of Amerindian sites on Dos Mosquises Island, Los Roques Archipelago, Venezuela, uncovered a wide range of evidence reflecting seasonal exploitation of local resources and multiple ritual depositions of large quantities of ceramic figurines, lithics, and faunal remains. Zooarchaeological analysis revealed the presence of modified and unmodified bones and teeth from numerous imported mammal species. Local geographic and environmental conditions preclude permanent establishment of terres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 85 publications
1
18
0
Order By: Relevance
“…From an archaeological perspective, the late pre-Hispanic inhabitants of north-central Venezuela were integrated within the Valencioid Sphere of Interaction as defined by Antczak and Antczak (1999;see also Guzzo Falci et al 2017;Laffoon et al 2016). They were associated with the western segment of northern Cariban-speakers, and linked to the protohistoric Caraca Amerindians (Antczak 1999;Biord 2001).…”
Section: Cariban-speakers In North-central Venezuelamentioning
confidence: 99%
“…From an archaeological perspective, the late pre-Hispanic inhabitants of north-central Venezuela were integrated within the Valencioid Sphere of Interaction as defined by Antczak and Antczak (1999;see also Guzzo Falci et al 2017;Laffoon et al 2016). They were associated with the western segment of northern Cariban-speakers, and linked to the protohistoric Caraca Amerindians (Antczak 1999;Biord 2001).…”
Section: Cariban-speakers In North-central Venezuelamentioning
confidence: 99%
“…More recently, a broader range of biomolecular methods and approaches have been applied to the Caribbean faunal record to investigate various topics pertaining to patterns of animal paleomobility. These latter include genetic (Kimura et al 2016) and isotopic studies of the anthropogenic introduction of wild or commensal species ; see also Giovas, 2017) and domesticated species (Laffoon et al 2015), and the transport/exchange of animal skeletal resources and artefacts (Laffoon et al 2014, Laffoon, Sonnemann et al 2016. However, to our knowledge, no studies to date have explicitly explored correspondences and contrasts between humans and animals in this region by combining strontium and carbon isotopes analyses.…”
Section: Introductionmentioning
confidence: 99%
“…For example, recent research (Mickleburgh and Laffoon 2017) has demonstrated that 'Archaic' individuals from Aruba, where multiple lines of archaeological and bioarchaeological evidence have previously suggested distinct hunter-gatherer subsistence practices and highly marine-reliant diets, also possessed extremely enriched enamel δ 13 C values (−5.3 to −3.9‰). In recent years, strontium isotope ( 87 Sr/ 86 Sr) approaches have also been widely applied to studies of human and animal paleomobility, and artefact provenance studies in the Caribbean (Booden et al 2008;Giovas et al 2016;Hofman et al 2012;Hoogland, Hofman, and Panhuysen 2010;Laffoon 2012Laffoon , 2013Laffoon , 2016Laffoon et al , 2014Laffoon et al , 2015Laffoon et al , 2017Laffoon, Sonnemann et al 2016;Valcárcel Rojas et al 2011). The Caribbean region is particularly well suited to the application of the strontium isotope method owing to the geological diversity (Donovan and Jackson 1994) and hence high degree of variability and spatial pattering of bedrock and bioavailable 87 Sr/ 86 Sr. For this region, both large-scale empirical datasets and spatially explicit predictive models of regional isotope landscapes (isoscapes), of bioavailable 87 Sr/ 86 Sr have been developed (Bataille, Laffoon, and Bowen 2012;.…”
mentioning
confidence: 99%
“…Similar approaches were used to identify the geographical origins of a pre-colonial deposition of faunal remains on Dos Mosquises Island, where no mammalian fauna was natively present, linking the island with the Lake Valencia Basin and suggesting the deposition of faunal remains might be linked to seasonal subsistence activities on the island by mainland communities (Laffoon et al, 2016). Long distance trade at the Maya site of Ceibal, Guatemala, specifically of non-local dogs, was also established using a similar multi-isotope framework (Sharpe et al, 2018 Oew that underpins the use of these methods in assigning geographical origin.…”
Section: Animal Origin and Animal Products: Exchange Transport Tradementioning
confidence: 99%